IMPLEMENTATION OF ORGANIC FARMING IN REALIZING SUSTAINABLE AGRICULTURE - Restu Jaya Zendrato; Putra Hidayat Telaumbanua; Helmin Parida Zebua; Ridho Victory Nazara; Marni Putri Gea (Jurnal Sapta Agrica, 2024)
Organic farming has become a major focus in efforts to overcome modern agricultural challenges related to environmental sustainability and human health. This article presents a literature review that aims to evaluate the contribution of organic farming in increasing agricultural productivity and environmental sustainability. This article aims to inform farmers about maintaining agricultural sustainability in the long term by maintaining soil fertility, reducing carbon footprints, and improving human health through organic food